Vanishing twin syndrome is associated with first-trimester intrauterine hematoma in twin pregnancies after in vitro fertilization - Ge, Yimeng; Lai, Shaoyang; Li, Xiaoxue; Shi, Jing; Ma, Caihong; Zhao, Jie (Frontiers in Endocrinology, 2023)
Research Question: Is there association between intrauterine hematoma(IUH), Vanishing Twin Syndrome(VTS) and subsequent complications in twin pregnancies after in vitro fertilization(IVF)? What are the risk factors for these complications? Design: Women presented with two live gestational sacs following double embryo transfer were included. Patients with systematic diseases, artificial fetal reduction and incomplete data were excluded. Further stratification of IUH pregnancies was done according to IUH-related characteristics(i.e. volume, changing pattern, relationship with fetal cardiac activities). The primary outcome was the incidence of VTS while adverse outcomes in the surviving singleton and the gestational age of VTS were secondary outcomes. Results: The incidence of IUH was 13.8%. A total of 1078 twin pregnancies including 539 IUH pregnancies and 539 non-IUH pregnancies were included. IUH pregnancy was associated with higher risks of VTS(26.9% vs 18.7%, p=0.001) as well as higher incidence of preterm birth(p=0.001, Crude OR=1.98 95%CI 1.28-3.09, Adjusted OR=1.19 95%CI 1.09-1.24), threatened abortion(p<0.001, Crude OR=9.12 95%CI 2.90-28.69, Adjusted OR=6.63 95%CI 1.69-14.67) and postpartum hemorrhage(p=0.024, Crude OR=3.13 95%CI 1.09-8.99, Adjusted OR=1.16 95%CI 1.08-1.32)in the surviving singleton. Risks of other complications weren’t of significant difference. The absence of fetal cardiac activities at the diagnosis of IUH predicted VTS(p<0.001, Crude OR 4.67 95%CI 3.67-5.78, Adjusted OR 3.33 95%CI 1.56-5.14) and fetal loss at smaller gestational age(7.81±2.10 weeks vs 11.39±5.60 weeks, p<0.001), while an IUH with an increasing volume didn’t increase the risk of VTS but might induce threatened abortion in the surviving fetus(p<0.001, Crude OR 1.84 95%CI 1.32-2.55, Adjusted OR 1.72 95%CI 1.13-2.13). Conclusions: IUH was a risk factor for VTS in twin pregnancy following double embryo transfer, and elevated the risks of threatened abortion, preterm birth and postpartum hemorrhage in the surviving singleton. The absence of fetal cardiac activities at the diagnosis of IUH elevated the risks of VTS while an IUH with an increasing volume was associated with threatened abortion without elevating the risks of VTS. An IUH diagnosed before the presence of fetal cardiac activities also resulted in earlier miscarriage. The study suggests that attention be paid to twin pregnancies with first trimester IUH to prevent VTS and subsequent adverse perinatal outcomes.